A GENESIS OF GENERAL KKM THEOREMS FOR ABSTRACT CONVEX SPACES - Park, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In a recent work of the author [42], we obtained three general KKMtype theorems for abstract convex spaces. In this review, we show that two of them can be stated for intersectionally closedvaluedKKM maps in the sense of Luc et al. [13]. Each of such KKM type theorems contains a large number of previously known particular forms. We recall some of them due to the author in order to give a short history on such theorems. Further comments on related works are given.